Essays on equality of opportunity - Paul Hufe (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2021)
Equality of opportunity is a principle of justice that is built on two fundamental ideas. On the one hand, outcome differences across individuals are unacceptable if they are rooted in factors that are beyond individual control. Examples of such circumstance characteristics are the biological sex, race, and the socio-economic status of one's parents. On the other hand, if individual outcomes were the result of effort, proponents of an equal-opportunity ethic would accept outcome differences across individuals as fair.
Keywords: C38; D31; D63; I32; J13; J16; J22; J24; 330; Inequality; Equality of Opportunity; Poverty; Fairness; Measurement; Machine Learning; Random Forests; Family Decision-Making; Gender Wage Gap; Skill Formation